The mechanism of the preventive effect of Shen'an capsule on the calcium oxalate crystal‐induced early renal injury based on metabolomics. (17th October 2018) - Fan, Wei; Hou, Jiebin; Zhu, Weiye; Zhang, Shuyue; Shao, Keda; Quan, Feiyu; Chen, Wei
Abstract: Kidney stone disease is a worldwide metabolism‐associated disorder with a high incidence of renal dysfunction. However, effective methods to prevent crystalline nephropathy are still lacking owing to the absence of aetiological research. Shen'an (SA) capsules are prepared from Chinese medicinal compounds and are considered a promising treatment for the prevention of crystal‐induced renal injury. In this study, 24 mice were randomly divided into four groups: saline, oxalate, SA‐treated (via preventive administration) and SA‐only groups. A metabolomics analysis based on ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry (UPLC‐Q‐TOF/MS) was performed to explore the plasma metabolic profiles among the different groups. The amount of crystal deposition and the decline in kidney function were significantly alleviated by the use of SA capsule. A total of 24 metabolites that showed a reversal trend following SA capsule administration were identified as plasma biomarkerss of the preventive effects of SA capsules on crystal‐induced renal injury. Most of these metabolites were involved in the metabolisms of lipid metabolism, energy metabolism, glutathione metabolism and vitamin metabolism. In conclusion, SA capsules exert a preventive effect in mice with crystal‐induced kidney injury via the regulation of multiple metabolic pathways.